Uso de coleções virtuais como ferramentas didáticas no ensino de Botânica - Lacerda, Nadja Larice Simão de (2019)
Botany is the area of biology in charge of the study of plants in their various aspects, morphological, anatomical, physiological and ecological. The traditional, contentless and decontextualized way in which Botany classes are regularly taught has been a limiting factor in the construction of knowledge. In this scenario, the teacher faces the challenge of seeking methodological strategies and pedagogical tools that contribute to the construction of meaningful learning that arouses students' interest in vegetables. This work aimed to assemble and use virtual biological collections as didactic tools for the improvement and contextualization of Botanic teaching and was carried out between August 2018 and May 2019, with students from three high school second grade classes, (when the project was completed the students were already in the third grade of high school) from a public school in the city of Bonito de Santa Fe, in the state of Paraiba. The execution of the activities was based on the mixed approach of the research. As a methodological strategy it was opted for action research. Data were obtained through questionnaires. The work sought to establish relationships between the contents approached in the classroom and the local reality experienced by the students, through knowledge and appreciation of the vegetal biodiversity of the region, through a diversified set of methodological strategies including lectures and dialogues, pedagogical workshops, field classes and the construction of biological collections. Theoretical expositions were made using audiovisual resources; dialogues through debates on the economic and ecological importance and the need for conservation of native caatinga species; pedagogical workshops with techniques of herborization and collection; and field classes for photographic recording of species and gathering of specimens for the preparation of biological collections. Finalizing the pedagogical intervention were produced three biological collections, an herbarium, a carpoteca and seed library of caatinga plants, which were later made available in a blog in the form of virtual collections, in order to promote a direct interaction between students and Information and Communication Technologies (ICT). After a comparative analysis of the pretest and posttest, it was revealed that the use of active methodologies is a viable pedagogical option for the teaching of Botany, since it promotes a more contextualized teaching, contributing to a better understanding of the studied contents and favoring the protagonism of the students in the construction of knowledge